Turkey and the changing energy geopolitics of Eurasia - ERŞEN, EMRE (ELSEVIER SCI LTD, 2019)
While Turkeys geographical location is usually viewed as a major advantage in the energy sphere, since many countries in its immediate neighbourhood require active Turkish collaboration in order to export or import oil and natural gas via economically feasible pipeline projects, the ongoing political, economic and military conflicts between the same global and regional actors not only negatively affect the development of the energy transportation routes in Eurasia, but also present a major foreign policy challenge for Ankara that has traditionally sought to maintain a careful balance in its relations with the West and Russia. The goal of this article is to elaborate on the influence of such geopolitical factors in evaluating Turkeys role in terms of the oil and natural gas pipelines that are either planned or already under construction to connect the various sub-regions of Eurasia. Employing a traditional geopolitical approach, it seeks to understand what kind of geopolitical factors come into play regarding Turkey's role in the changing energy geopolitics of Eurasia and in what ways these geopolitical factors strengthen or weaken Turkeys objective to be perceived as a regional energy hub by other actors.
Keywords: Turkish foreign policy; Energy; Oil and natural gas pipelines; Southern gas corridor; Turkish stream; Eurasian geopolitics; FOREIGN-POLICY; GREAT GAME; CONFLICT; STRATEGY; PIPELINE; VISION; RUSSIA; HUB